Empowering Women Agripreneurs through Government Livelihood Initiatives: A Case Study of Jharkhand, India - Bihari, Bipin; Priya, Anusha; Jha, Basant Kumar; Kumar, Avinash; Mishra, Shivam (Indian Journal of Extension Education, 2024)
The study evaluates the impacts of targeted interventions implemented by the Central and state government in Jharkhand, India. Being a part of Ph.D. thesis, 260 beneficiaries from 13 blocks in three districts of Jharkhand were selected, and data was conducted during the year 2023-24. Conclusions were derived using descriptive and inferential statistics. The research revealed that all respondents were beneficiaries of the National Rural Livelihood Mission (NRLM), followed by Jharkhand Opportunities for Harnessing Rural Growth (JOHAR) (92.7%) and Jharkhand Horticulture Intensification by Micro Drip Irrigation (JHIMDI) (14.2%). The investigation also identified a substantial increase in the ownership of assets such as poly houses, poultry sheds, and micro drip systems. Income, expenditure, and savings in these areas demonstrated statistical significance after association with the programs. Income in agriculture, livestock, fisheries, and agribusiness improved significantly after receiving benefits. Principal component analysis identified three principal components with Eigen values > 1.0, with a cumulative variance of 71.03. Four entrepreneurial behavior traits-Innovativeness, Risk-bearing ability, Self-confidence, and Planning Orientation-were highly influenced by Principal Component 1, explaining 29.6 per cent of the total variance.
Keywords: Women agripreneur; Jharkhand; Benefit; Livelihood programs; Rural development; Gender equity